1996
DOI: 10.1074/jbc.271.49.31086
|View full text |Cite
|
Sign up to set email alerts
|

The Inactive pT181 Initiator Heterodimer, RepC/C, Binds but Fails to Induce Melting of the Plasmid Replication Origin

Abstract: Staphylococcus aureus plasmid pT181 replicates via a rolling circle mechanism. The synthesis of the pT181 initiator protein (RepC) is regulated by antisense RNAs, and RepC is inactivated after usage by the attachment of an oligonucleotide to one of its subunits. The inactivated heterodimeric RepC/C* has been shown be unable to initiate replication in vitro (Rasooly, A., and Novick, R. P. (1993) Science 262, 1048 -1050). The inactive RepC/C* has been found to be very stable and constitute about 90 -95% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…7). The above results are consistent with the previous observation that RepC binds to both the IRIII and IRII regions in supercoiled DNA, whereas RepC/RepC* binds only to the IRIII region (29). The inability of RepC/RepC* to bind to IRII and oligomerize on the DNA may result in a lack of melting of the pT181 origin involving IRII, which is critical for nicking by the initiator protein.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…7). The above results are consistent with the previous observation that RepC binds to both the IRIII and IRII regions in supercoiled DNA, whereas RepC/RepC* binds only to the IRIII region (29). The inability of RepC/RepC* to bind to IRII and oligomerize on the DNA may result in a lack of melting of the pT181 origin involving IRII, which is critical for nicking by the initiator protein.…”
Section: Discussionsupporting
confidence: 82%
“…Based on this and other findings, it has been proposed that RepC exists as a dimer in solution and that attachment of the oligonucleotide to one subunit results in the inactivation of the other, wild-type subunit by an as yet unknown mechanism (25,27). Recently, the RepC/RepC* heterodimer isolated from pT181-containing cells was found to retain its DNA binding activity but was defective in its ability to induce cruciform extrusion at the origin (25,28,29). Since preparations of RepC* from pT181-containing cells always contain a 1:1 mixture of RepC and RepC* forms, we have generated RepC* in vitro.…”
mentioning
confidence: 99%
“…As can be seen, the retarded RepC/C* band in lane 3 is much weaker than the RepC/C-DNA band in lane 1, indicating that the affinity of RepC/C* for DNA is less than 50% of that of RepC/C. We have calculated that the binding constants of the two forms actually differ by a factor of about 4 (10).…”
Section: Quantitation Of Repcmentioning
confidence: 81%
“…Thus, the second transesterification allows completion of the termination process by avoiding recycling, i.e., continuous synthesis of the leading strand driven by the same initiator molecule (117). Analysis of the different interaction patterns of RepC/C and RepC/C* with the pT181-dso DNA by in vitro footprinting and binding-bending assays revealed that, although RepC/C* retains the ability to bind to DNA, it is unable to promote cruciform extrusion to expose the nick sequence in ssDNA form (118). This may explain why the formation of a RepC/ RepC* heterodimer inactivates the protein in addition to uncoupling termination of leading-strand replication and initiation of a new replicative round.…”
Section: Mechanisms That Restrict the Use Of Rep Molecules To A Singlmentioning
confidence: 99%